Analisis Kesulitan yang Dihadapi pada Siswa Kelas V dalam Pembelajaran Bangun Ruang - Unaenah, Een; Kumarani, Nanda Citra; Wulandari, Sri (Lembaga Yasin AlSys, 2023)
Students' inability to comprehend the nature of abstract geometry and the unstable nature of the concept of geometric properties are the driving forces behind this study. It is anticipated that geometry teaching aids will enhance teacher performance, learning outcomes for students, and learning activities for students. use math instruments to further develop learning results, understudy learning exercises, and instructor execution. Two brothers assisted in the execution of this exercise. According to the findings of this study, the BES (Education Guidance) tutoring center in the Batu Ceper area of Tangerang has students' comprehension of class V mathematical concepts. Both succeeded, however coming up short on vital information to figure out this mathematical shape. Information handling procedures use methods for perception and tests. Qualitative analysis methods were used to analyze the data. In light of perceptions and tests, 75% of respondents had the option to figure out math, while 25% of respondents couldn't comprehend arithmetic in view of one of the variables above.